Viral regulation of host cell biology by hijacking of the nucleolar DNA-damage response - Stephen M. Rawlinson (Nature Portfolio, 2018)
Many RNA viruses that replicate in the cytoplasm express proteins that localize to nucleoli, but the nucleolar functions remain largely unknown. Here, the authors show that the Henipavirus matrix protein mimics an endogenous Treacle partner of the DNA-damage response, resulting in suppression of rRNA biogenesis.